OPTIMIZATION OF COLONY POLYMERASE CHAIN REACTION FOR THE 16SRRNA OF DIFFERENT STRAINS OF ESCHERICHIA COLI - ULLAH, AMIN; BASHIR, AQIB; REHMAN, BILAL; NAEEM, WAFA; ZARA SHAH, SAMAN (Innovare Journal of Life Sciences, 2023)
Objective: This work aimed to enhance colony polymerase chain reaction (PCR) for the 16S rRNA of several Escherichia coli strains. Methods: The isolation of E. coli is done from the gut of the chicken and soil. Then, we optimized the condition for colony PCR for the amplification of 16s ribosomal RNA. We successfully designed primer 3 for 16s ribosomal RNA and made the dilution solution with PCR grade water that is 1:10. Moreover, finally, we made a 20 μL solution that contains the master mix of our isolated colony and forward and reverse base primer for amplification. After the conventional PCR, the amplified 16s ribosomal RNA was then run on Gel to obtain the desired bands. And finally saw the bands in the Gel Doc picture. Results: Our result shows that the technique of colony PCR is an efficient and quick method than other existing methods that are too costly, tedious, and time-consuming procedures that deter their exploitation in various experimentations and for the identification of E. coli strains. Conclusion: This study concluded that 16s ribosomal RNA can be amplified without the extraction and purification of total genomic DNA from a bacterial colony using colony PCR. Therefore, by designing rRNA primers for E. coli species, we can evaluate their various types of mutations, strain detection, and antibiotic resistance.